2020
DOI: 10.1186/s12863-020-0817-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL TGW12 responsible for grain weight in rice based on recombinant inbred line population crossed by wild rice (Oryza minuta) introgression line K1561 and indica rice G1025

Abstract: Background: Limited genetic resource in the cultivated rice may hinder further yield improvement. Some valuable genes that contribute to rice yield may be lost or lacked in the cultivated rice. Identification of the quantitative trait locus (QTL) for yield-related traits such as thousand-grain weight (TGW) from wild rice speices is desired for rice yield improvement. Results: In this study, sixteen TGW QTL were identified from a recombinant inbred line (RIL) population derived from the cross between the introg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…As we mentioned earlier, three lead SNP loci in chromosome 5 (chr05_9776079, chr05_1025757, and chr05_23772096) were significantly associated with both GWT and GL. As was observed for GL and GW, our association study on GWT presents some congruent results with respect to the previous studies [29, 30], in addition to revealing new chromosomal regions associated with GWT.…”
Section: Resultssupporting
confidence: 89%
“…As we mentioned earlier, three lead SNP loci in chromosome 5 (chr05_9776079, chr05_1025757, and chr05_23772096) were significantly associated with both GWT and GL. As was observed for GL and GW, our association study on GWT presents some congruent results with respect to the previous studies [29, 30], in addition to revealing new chromosomal regions associated with GWT.…”
Section: Resultssupporting
confidence: 89%
“…Based on these or similar studies, many TGW-associated genes of rice have been cloned, such as the RING-type E3 ubiquitin ligase OsGW2 ( Song et al, 2007 ), the arginine-rich domain nuclear protein OsGW5 ( Shomura et al, 2008 ), the SBP domain transcription factor OsGW8 ( Wang et al, 2012 ), and the indole-3-acetic acid (IAA)-glucose hydrolase protein OsTGW6 ( Ishimaru et al, 2013 ). To date, QTLs/genes associated with TGW have been mostly cloned from cultivated rice ( Li et al, 2020 ). Compared with related research in rice, the QTLs and molecular cloning of genes associated with TGW are lacking for maize ( Guo et al, 2011 ; Liu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Grain weight is a synthetic reflect of grain length, width, thickness and plumpness. All these traits have been comprehensively studied using bi-parental populations through QTL mapping (Xing et al 2002;Li et al 2004Li et al , 2020Weng et al 2008;Wang et al 2011;Tang et al 2013;Xu et al 2015;Dong et al 2018;Bazrkar-Khatibani et al 2019), and hundreds of QTLs related to these traits were reported and stored in the Gramene QTL Database (Gupta et al 2016).…”
Section: Introductionmentioning
confidence: 99%